Engaging learning experience: Students’ perception and readiness towards implementation of blended learning in interior design course at UiTM Seri Iskandar, Perak Malaysia - Ahmad, Norfazillah; Awang, Arita Hanim (2018)
Blended learning are widely implemented in higher level of education. Referred to many researches, blended learning means the combination of face to face classroom learning and e-learning. Technology has become natural to students nowadays and social interaction through various medium becoming part of learning process. Students’ learning characters are changing by the rapid technology growth in our lifestyle. This trend leading to new learning environment in various courses as well as Interior Design course. In the nature of studio learning, engaging the students throughout the designing process is significant so the learning experience can be more meaningful. This paper conduct a study on the implementation of blended learning in Interior Design (ID) course in UiTM Seri Iskandar, Perak with the objectives (1) to investigate students’ perceptions and readiness towards blended learning implementation in ID course and (2) to promote a meaningful learning experience to the student. 90 final year students were involved in this engaging learning experience study. Study conducted on 90 final year students for Interior Design course through questionnaire survey after the implementation of blended learning for the course by the end of semester. Findings shows positive responses in students’ perceptions and readiness towards the blended learning implementation and its encouraging students becoming more constructive and productive. Students are positive that blended learning in Interior Design studio has maximize their engagement in the learning process.